Implementation of the principle of presumption of innocence of suspects in investigations, pre-trial and trial examinations - Sukadana, Dewa Ayu Putri (Institute Of computer Science (IOCS), 2024)
The principle of presumption of innocence is a fundamental legal principle in the justice system to protect the rights of suspects. Law No. 8 of 1981 concerning Criminal Procedure Law (KUHAP) Article 66 of the Criminal Procedure Code explains